1987
DOI: 10.1139/v87-124
|View full text |Cite
|
Sign up to set email alerts
|

Facile calculations of select eigenvalues and the characteristic polynomial of small molecular graphs containing heteroatoms

Abstract: JERRY RAY DIAS. 1987. Can. J. Chem. 65, 734 (1987. Determination of common eigenvalues by embedding smaller subgraphs onto larger ones is illustrated. A nearly universal expression of the sixth coefficient of the characteristic polynomial valid for all conjugated hydrocarbon polyenes is presented. Its use in a graph theoretical determination of the Huckel MO characteristic polynomial of molecular graphs possessing heteroatoms is detailed.JERRY RAY DIAS. 1987. Can. J. Chem. 65, 734 (1987 On illustre comment on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Such molecular graphs can be represented by vertex- and edge-weighted graphs . Dias established a way of obtaining the characteristic polynomial for a molecular graph perturbed by a heteroatom from the characteristic polynomial for the isoconjugate graph (a graph in which the heteroatom is replaced with the carbon atom) and that for the graph obtained upon deletion of heteroatom vertex with its adjacent edges . In this context, the isoconjugate graph corresponds to an unperturbed system.…”
Section: Hückel Mo Perturbation Theory and Its Impact On Qimentioning
confidence: 99%
“…Such molecular graphs can be represented by vertex- and edge-weighted graphs . Dias established a way of obtaining the characteristic polynomial for a molecular graph perturbed by a heteroatom from the characteristic polynomial for the isoconjugate graph (a graph in which the heteroatom is replaced with the carbon atom) and that for the graph obtained upon deletion of heteroatom vertex with its adjacent edges . In this context, the isoconjugate graph corresponds to an unperturbed system.…”
Section: Hückel Mo Perturbation Theory and Its Impact On Qimentioning
confidence: 99%
“…This procedure is specific for the acyclic polynomial, without an equivalent version for the characteristic polynomials in the general case. 26 Use of eqn ( 6) until all the cycles have been opened leads to an expression for P ac (x) as a weighted sum of characteristic polynomials (for open-chain fragments, the acyclic and characteristic polynomials are equal). Since characteristic polynomials have a strong chemical relevance, it is clear that eqn (6) is of not only practical, but also of fundamental importance as it provides TRE with a definite, if indirect chemical interpretation.…”
Section: Graph-theoretical Backgrounds Of Trementioning
confidence: 99%
“…For the unique C 20 fullerene, the first eight coefficients have the same absolute values. Balasubramanian, 19 adapting work published by Dias,20 showed that these coefficients for characteristic polynomials of all C n fullerenes depend only on n. His formulas may also apply to the permanental polynomials, but that has yet to be determined.…”
Section: Resultsmentioning
confidence: 99%